The Influence of Motivation and Work Discipline on Em-ployee Performance at the Department of Manpower and Transmigration Karawang Regency - Siti Annisa; Asep Jamaludin; Yeni Fajrin (International Journal of Economics and Management Research, 2025)
Investigating and evaluating the effects of work discipline and motivation on employee performance at Karawang Regency's Department of Manpower and Transmigration is the aim of this study. The study was prompted by the urgent need to address the issue of low staff productivity. The methodology used is a descriptive research with a quantitative experimental approach. The saturation sampling technique, which uses the entire population as the sample, was used to select the 100 respondents in total. Data was collected by questionnaires, and the results were analyzed using descriptive interpretation and multiple linear regression tests in SPSS version 25. Based on the validity test results, 15 items for each variable motivation, work discipline, and employee performance were declared valid, and all items were found to be reliable. The data analysis results indicated that the significance values for motivation (X1) and work discipline (X2) were both 0.000. Since these values are less than 0.05, it can be concluded that both factors have a considerable effect on employee performance. These findings support the notion that more employee motivation and discipline translate into improved performance. With the best motivation and discipline, the Department of Manpower and Transmigration at Karawang Regency will be more productive.